Making space for disability in eco‐homes and eco‐communities. Issue 4 (15th September 2015) - Bhakta, Amita; Pickerill, Jenny
Abstract : There is continued failure to build homes for diverse and disabled occupancy. We use three eco‐communities in England to explore how their eco‐houses and wider community spaces accommodate the complex disability of hypotonic cerebral palsy. Using site visits, video footage, spatial mapping, field diary observations, surveys and interviews, this paper argues that little attention has been paid to making eco‐communities and eco‐houses accessible. There are, we argue, three useful and productive ways to interrogate accessibility in eco‐communities, through understandings of legislation, barriers and mobility. These have three significant consequences for eco‐communities and disabled access: ecological living as practised by these eco‐communities relies upon particular bodily capacities, and thus excludes many disabled people; disabled access was only considered in relation to the house and its thresholds, not to the much broader space of the home; and eco‐communities need to be, and would benefit from being, spaces of diverse interaction.